Radiogenomics – current status, challenges and future directions. Issue 1 (1st November 2016) - Andreassen, Christian Nicolaj; Schack, Line Meinertz Hybel; Laursen, Louise Vagner; Alsner, Jan
Highlights: Radiogenomics is a scientific field related to radiobiology. It addresses associations between genetic variants and normal tissue radiosensitivity. More than 130 original papers have been published on this topic. Several compelling associations have been reported. Abstract: Radiogenomics designates a scientific field that addresses possible associations between genetic germline alterations and normal tissue toxicity after radiotherapy. The ultimate aim of this research is to establish a gene-based predictive test for normal tissue radiosensitivity. During the last 5 years, substantial progress has been achieved in this field. Several compelling associations for SNPs have been demonstrated in large candidate gene studies as well as genome wide association studies. These findings shed new light on radiobiology and expand our understanding of the processes that lead to side effects after radiotherapy. Despite this, certain fundamental challenges still relate to genomic approaches. Based on the latest insights into complex trait genetics and molecular genetics, we provide an analysis of these challenges and propose putative strategies to further advance the field. These strategies include 'big data approaches' and collaborative research within international consortia. Furthermore, research that combines the study of radiation-induced gene expression and genome-wide SNP genotype may discover genetic alterations that regulate the biological response to ionizing radiation. Thus, such integrative approaches may lead to genetic alterations that affect risk of normal tissue toxicity.